Організаційно-правові основи морського агентування - Сергєєва, Наталія Миколаївна; Сергеева, Наталия Николаевна; Sergeeva, Natalia M. (My University, 2000)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.07 - теорія управління; адміністративне право і процес; фінансове право. - Одеська національна юридична академія, Одеса, 2000. У дисертації проводиться аналіз організаційно-правових основ морського агентування - інституту адміністративного права, регулювання якого істотно змінилося за останні роки. Комплексно розглядаються взаємовідносини держаних органів і суднових агентів при здійсненні адміністративно-правового регулювання морського агентування, визначається специфіка організаційно-правових засобів і методів регулювання діяльності суднових агентів та пропонуються заходи щодо вдосконалення законодавства України з питань морського агентування.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.07 - теория управления; административное право и процесс; финансовое право. - Одесская национальная юридическая академия, Одесса, 2000. В диссертации проводится анализ организационно-правовых основ морского агентирования - института административного права, регулирование которого существенно изменилось в последние годы. Комплексно рассматриваются взаимоотношения государственных органов и судовых агентов при осуществлении административно-правового регулирования морского агентирования, определяется специфика организационно-правовых средств и методов регулирования деятельности судовых агентов и предлагаются меры по совершенствованию законодательства Украины по вопросам морского агентирования.

Thesis for a Candidate of Law's degree by specialized 12.00.07 - Theory of Management; Administrative Law and Process; Financial Law. - Odessa National Law Academy, Odessa, 2000. From the point of view of the science of administration and law and the science of maritime law this paper is the first complex research of organizational and legal bases of ships' agency service. It is noted that in the legal literature, as a whole, problems of ships' agency service have not been discussed from the standpoint of its organizational and legal bases, therefore the science of law has no developed conceptual provisions connected with organizational and legal status of a ship agent, there are no elaborations as for specificity of the state regulation of ships' agency service, its foundations and limits. The thesis discloses the notion substance of a ship agent, clarifies the essence of ships' agency service, points out specific functions of a ship agent which are of administrative nature. There are revealed historical preconditions of ships' agency service, the history of legal regulation of ships' agency service is given, the process of ships' agency service formation as an independent kind of activity is discussed. The thesis lists the comparative characteristic of legal acts, as well as methods of state regulation of ships' agency service in various countries of the world: Belgium, Great Britain, Germany, Holland, Denmark, Italy, Russia, France, Sweden, Japan. There is given an analysis of effective normative legal acts of Ukraine which establish the procedure for implementation of ships' agency service in Ukraine, as well as legal means of its state regulation are determined. The thesis gives compound consideration of mutual relations between state bodies and ship agents when implementing processes of state registration of subjects of ships' agency service, licensing of ships' agency service, control on the part of authorized state bodies over the activity of ship agents and implementation of other means and methods of administrative and legal regulation with respect to ship agents when they perform their functions in organizing and coordinating all operations connected with supply and services of ships, as well as proposes measures for perfection of means of legal regulation of ships' agency service and their use. Proposals are made as for the necessity to simplify state legitimacy of the subjects of ships' agency service activity, to perfect criteria for referring agency service of the merchant marine to licensed types of activity, to introduce definite qualification requirements to persons exercising ships' agency service, to adopt a professional code of conduct for ship agents proceeding from their special status and specifics of activity, as well as the necessity to observe international standards for ship agents.
Сергєєва Н. М. Організаційно-правові основи морського агентування : автореф. дис. ... канд. юрид. наук : 12.00.07 / Н. М. Сергєєва; кер. роботи Є. В. Додін; Нац. ун.-т "Одеська юридична академія". – Одеса, 2000. – 21 с.
Keywords: морське агентування; судновий агент; адміністративні функції; адміністративно-правове регулювання; державний вплив; організаційно-правові основи; адміністративна відповідальність; підприємництво; ліцензування; міжнародні стандарти; морское агентирование; судовой агент; административные функции; административно-правовое регулирование; государственное воздействие; организационно-правовые основы; административная ответственность; предпринимательство; лицензирование; международные стандарты; ships' agency service; ship agent; administrative functions; administrative and legal regulation; state influence; organizational and legal bases; administrative responsibility; enterprise; licensing; international standards